2001
DOI: 10.1523/jneurosci.21-13-04801.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Code for Behavioral Inhibition on the Basis of Color, But Not Motion, in Ventrolateral Prefrontal Cortex of Macaque Monkey

Abstract: To examine the neural mechanism for behavioral inhibition, we recorded single-cell activity in macaque ventrolateral prefrontal cortex, which is known to receive visual information directly from the inferotemporal cortex. In response to a moving random pattern of colored dots, monkeys had to make a go or no-go response. In the color condition, green indicated go, whereas red indicated no-go, regardless of the motion direction; in the motion condition, upward indicated go, whereas downward indicated no-go, rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
71
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 57 publications
12
71
1
Order By: Relevance
“…This finding of transformation of visual information into behavior-specific information agrees with previous reports showing that the lPFC is involved in categorizing visual objects (Freedman et al, 2001), integrating visual objects and saccade directions (Asaad et al, 1998), determining GO/NOGO responses based on visual object signals (Sakagami et al, 2001), shifting cognitive set according to sensory feedback (Konishi et al, 1996;Nakahara et al, 2002), retrieving or selecting task-relevant information based on sensory signals (Thompson-Schill et al, 1998;Rushworth et al, 2005), and selecting the direction of saccades in a strategic manner based on visual stimuli (Genovesio et al, 2005). In other reports, sensory signals used as an instruction cue were found to generate information that specifies the behavioral rule [i.e., to follow either a spatial rule or a conditional rule (White and Wise, 1999) or to select a matching-to-sample rule or a non-matching-to-sample rule (Wallis et al, 2001;Bunge et al, 2003) in performing a forthcoming behavioral task].…”
Section: Involvement Of the Three Areas In Retrieving Behavioral Goalsupporting
confidence: 92%
“…This finding of transformation of visual information into behavior-specific information agrees with previous reports showing that the lPFC is involved in categorizing visual objects (Freedman et al, 2001), integrating visual objects and saccade directions (Asaad et al, 1998), determining GO/NOGO responses based on visual object signals (Sakagami et al, 2001), shifting cognitive set according to sensory feedback (Konishi et al, 1996;Nakahara et al, 2002), retrieving or selecting task-relevant information based on sensory signals (Thompson-Schill et al, 1998;Rushworth et al, 2005), and selecting the direction of saccades in a strategic manner based on visual stimuli (Genovesio et al, 2005). In other reports, sensory signals used as an instruction cue were found to generate information that specifies the behavioral rule [i.e., to follow either a spatial rule or a conditional rule (White and Wise, 1999) or to select a matching-to-sample rule or a non-matching-to-sample rule (Wallis et al, 2001;Bunge et al, 2003) in performing a forthcoming behavioral task].…”
Section: Involvement Of the Three Areas In Retrieving Behavioral Goalsupporting
confidence: 92%
“…Lateral PFC regions appear to support inhibition in these paradigms. In monkeys, electrical potentials elicited by nogo stimuli were recorded from both the DLPFC and VLPFC regions, and electrically stimulating these regions approximately 100 ms after presentation of the go stimulus resulted in complete cancellation or dramatic delay of the go response (Sasaki, Gemba, & Tsujimoto, 1989; see also Sakagami, Tsutsui, Lauwereyns, Koizumi, Kobayashi, & Hikosaka, 2001). Similarly, an fMRI study of macaques found that relative to go trials, nogo trials elicited strong activity in bilateral VLPFC (Morita, Nakahara, & Hayashi, 2004).…”
Section: Neurobiological Mechanisms Of Response Inhibitionmentioning
confidence: 96%
“…Neural recording studies in monkey ventrolateral PFC have shown increased cellular firing rates during NoGo trials for manual and oculomotor paradigms (Sakagami et al, 2001). Many studies in the monkey have used an oculomotor version of the Stop signal paradigm to investigate neural activity on Go and Stop trials and to reveal signals for movement production, reward, monitoring, and control (for review, see Schall et al, 2002).…”
Section: Neurophysiological Mechanisms Of Stoppingmentioning
confidence: 99%